Characterisation of Semigroups and Rings - K. V. R. Srinivas (Characterisation of Semigroups and Rings, 2023)
In Algebra Groups & Rings Plays Important Rolle. In This Book mainly we have obtained important results, properties & charecterazations Semi Groups & Rings. In This Book we have obtained charecterazation of Partial orders in regular Semi Groups which is obtained as Chapter-1. In This Book we have obtained charecterazation of Ideal Semi Groups of Inverse Semi Groups which is obtained in Chapter-2. We also obtained Equalent Identies of Semi Rings which is obtained in Chapter-3. We also obtained certain Equavalent conditions On Commutativity of Associative Rings which obtained in Chapter-4. Finally in This Book we have obtained Properties of Distributive, Neutral and Standard Elements of a Lattice which is obtained as Chapter-5.